Implementasi Community Relations melalui Workshop Penyusunan Curriculum Vitae bagi Pemuda Desa Waluya - Suci Baby Arabella; Deddy Agus Purwanto (GLOBAL SCIENTS PUBLISHER, 2026)
Work readiness is one of the challenges faced by young people, particularly in understanding the professional documents required during the recruitment process. Based on observations conducted in Waluya Village, Cicalengka District, Bandung Regency, it was found that some youths lacked understanding of the importance of a Curriculum Vitae (CV), were unable to distinguish between an Applicant Tracking System (ATS)-friendly CV and a Creative CV, and had low awareness of the importance of personal branding. This article aims to describe the implementation of Community Relations through a Curriculum Vitae Preparation Workshop for the youth of Waluya Village. The study employed a qualitative descriptive approach, with data collected through observation, documentation, and activity evaluation. The workshop was held on May 17, 2025, at the Waluya Village Hall and involved 15 participants consisting of youth organization members (Karang Taruna) and unemployed young people. The materials delivered included an introduction to ATS-friendly CVs, Creative CVs, and personal branding. The results showed that participants gained a basic understanding of the functions of a CV, the differences between ATS-friendly and Creative CVs, and the importance of personal branding in preparing for the workforce. These findings indicate that the Community Relations approach can serve as an effective communication strategy in addressing community needs through relevant educational activities.